2022
DOI: 10.1021/acs.biomac.2c00150
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Poly(ester amide)s-Based Biomaterials

Abstract: Biodegradable and biocompatible biomaterials have offered much more opportunities from an engineering standpoint for treating diseases and maintaining health. Poly(ester amide)s (PEAs), as an outstanding family among such biomaterials, have risen overwhelmingly in the past decades. These synthetic polymers have easily and widely available raw materials and a diversity of synthetic approaches, which have attracted considerable attention. More importantly, combining the superiorities of polyamides and polyesters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 245 publications
(355 reference statements)
0
22
0
Order By: Relevance
“…A satisfactory biomaterial, after the full application in vivo, can often be degraded and absorbed by physical disintegration, biological mechanisms, and chemical reaction. Many of these biomaterials have been widely applied in practice, such as poly­(lactic- co -glycolic acid) (PLGA) (used for human body absorbable suture), poly­(lactic acid) (PLA) (used for absorbable screw), poly­(glycolic acid) (PGA) (used for bioabsorbable stents), and poly­(β-hydroxybutyrate) (PHB) (used for drug carrier or coating materials). There are still some biomaterials to be further developed, such as poly­(1,8-octanediol- co -citrate) (POC) as a thermosetting polyester.…”
Section: Introductionmentioning
confidence: 99%
“…A satisfactory biomaterial, after the full application in vivo, can often be degraded and absorbed by physical disintegration, biological mechanisms, and chemical reaction. Many of these biomaterials have been widely applied in practice, such as poly­(lactic- co -glycolic acid) (PLGA) (used for human body absorbable suture), poly­(lactic acid) (PLA) (used for absorbable screw), poly­(glycolic acid) (PGA) (used for bioabsorbable stents), and poly­(β-hydroxybutyrate) (PHB) (used for drug carrier or coating materials). There are still some biomaterials to be further developed, such as poly­(1,8-octanediol- co -citrate) (POC) as a thermosetting polyester.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely investigated as biodegradable materials for various applications such as drug delivery carriers, scaffolds for tissue engineering, and so forth. 1–5 PEAs can be synthesized via condensation polymerization of bifunctional monomers or ring-opening polymerization (ROP) of cyclic monomers. 1,2,6 Although many different bifunctional monomers ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely investigated as biodegradable materials for various applications such as drug delivery carriers, scaffolds for tissue engineering, and so forth. [1][2][3][4][5] PEAs can be synthesized via condensation polymerization of bifunctional monomers or ring-opening polymerization (ROP) of cyclic monomers. 1,2,6 Although many different bifunctional monomers (e.g., diacids, diols, amino acids, hydroxy acids, and amino alcohols) can be used to vary the polymer structures, the polycondensation usually proceeds slowly and shows poor control over the polymer molar mass and dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamides, which have repeated amide bonds and carbon linkages in the main chain, are one of the most widely used synthetic polymers in structural materials such as fibers for fabrics and fishing nets and industrial membranes due to their excellent mechanical and thermal properties. Since amide bonds can be hydrolyzed in the presence of water molecules, polyamides are considered to be a promising (bio)­degradable material. However, degradation is generally slower for polyamides than for other degradable polymers such as polyesters due to the strong intermolecular interactions and stable resonance structure in their chains . In fact, it has been reported that the most commercially used polyamide polymers such as polyamide 6 (PA6) and polyamide 66 are well decomposed only in some specific microorganism environments but not under marine conditions. …”
Section: Introductionmentioning
confidence: 99%